The Concept of Adequate Sustenance for The People with Social Welfare Problems (PMKS) (Study at Sukoharjo Urban Village Klojen Sub-District Malang City) - Al Chasna, Mienchah (Islamic Family Law Study Program, Sharia Faculty, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2019)
Every person has the right to carry out a marriage. The consequence of marriage is the emergence of rights and obligations between each other, one of which is the obligation to provide a sustenance. The obligation to provide a sustenance sometimes can be carried out by some people but it can also be an obstacle for those who have limited financial needs for instance the spouse with social welfare problems (PMKS). A lasting marriage with low economic conditions becomes interesting to study about how PMKS attempts to provide for family sustenance and how the concept of adequacy in the view of PMKS. This thesis uses a type of empirical research and a case study approach that focuses on a particular case to be observed and analyzed appropriately. The results of the study indicate that the efforts of People with Social Welfare Problems (PMKS) in fulfilling family sustenance are by working according to their respective abilities. Very few amounts of income is managed and intended for primary needs only, that is to afford daily food. While for clothing, residence, and conjugal sustenance, each PMKS has different ways to fulfilling it. The PMKS interpret adequacy is not feeling shortcome for anything. In low economic conditions, the majority of them are always grateful, so that they can feel enough even though they live in conditions of shortage.